If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 2x + -25 = x Reorder the terms: 12 + -25 + 2x = x Combine like terms: 12 + -25 = -13 -13 + 2x = x Solving -13 + 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -13 + 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x -13 + 1x = x + -1x Combine like terms: x + -1x = 0 -13 + 1x = 0 Add '13' to each side of the equation. -13 + 13 + 1x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 1x = 0 + 13 1x = 0 + 13 Combine like terms: 0 + 13 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 1-4(x+5)=6x-19 | | -3n-1=20 | | y-3.8-6=-1.9(y+6) | | (3n^2√2n^2)/√10n | | 9(8x-7)+10x= | | 2y+7+y-8-8= | | A=1/2bcd=bc;d | | nx^2=c-ny | | x-(1/3)=-0.5 | | 7x+6=12-3x+14 | | 8x^3-12x^2-6x=0 | | c-ny=nx^2 | | 2/3(x-3)-1/7(x+1)=1 | | 14+2x+30=x+32 | | 5x-3x+4=6x-1 | | 6x^2+45x+39=0 | | .75w-0.5w-4=12 | | -2P=Q-30 | | 4x-3y(4+y)=5 | | 2x^4+x^3-17x^2-4x+6=0 | | (7y-6v+6)(6y+7v)=0 | | x-c=yxc | | 3c+5-10c=-2 | | 1/3(3x-1)=(-1/4)-(1/4) | | 5a+4=-6 | | 1/x^2=27/x^5 | | -3+6(z+2)=6(-5z-1)-2 | | 1/3(3x-1)=-1/4-1/4 | | (z^(7/2))=5 | | 7x+6=12-3x+42 | | 2x+23+18+x=11 | | z^7/2=5 |